Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14112785
|View full text |Cite
|
Sign up to set email alerts
|

Hobnail Papillary Thyroid Carcinoma, A Systematic Review and Meta-Analysis

Abstract: Although papillary thyroid carcinoma (PTC) is considered to have an excellent prognosis, some recently identified more aggressive variants show reduced overall survival rates. Hobnail PTC (HPTC) was newly recognized as one of these aggressive forms, affecting recurrence, metastasis, and overall survival rates. Herein, we performed a systematic review and meta-analysis of studies including cases or case series with patients with HPTC. Furthermore, we included our individual case series consisting of six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…An ultrasound (US) scan and neck magnetic resonance imaging (MRI) scan pinpointed two additional heterogeneous 5–10 mm lymph nodes, as well as a 8 × 5 mm left submandibular lymph node with central vascularization. At this stage, the patient agreed to review the first histology, where a component of PDTC was seen ( Figure 1 ), along with hobnail and tall-cell variant features, as previously reported [ 34 ]. Importantly, the molecular and immunohistochemical analysis of previous biopsies showed a positive BRAFV600E mutation (exon 15, c.1799 T > A [p.V600E,COSM 476]).…”
Section: Case Presentationmentioning
confidence: 75%
See 1 more Smart Citation
“…An ultrasound (US) scan and neck magnetic resonance imaging (MRI) scan pinpointed two additional heterogeneous 5–10 mm lymph nodes, as well as a 8 × 5 mm left submandibular lymph node with central vascularization. At this stage, the patient agreed to review the first histology, where a component of PDTC was seen ( Figure 1 ), along with hobnail and tall-cell variant features, as previously reported [ 34 ]. Importantly, the molecular and immunohistochemical analysis of previous biopsies showed a positive BRAFV600E mutation (exon 15, c.1799 T > A [p.V600E,COSM 476]).…”
Section: Case Presentationmentioning
confidence: 75%
“…Our patient’s tumor histology was confirmatory of concurrent PDTC, hobnail, and tall-cell variant, all supportive of its aggressive nature, while all lymph node metastases from the first half of the long journey of this disease originated from the differentiated component of the tumor. The aggressive concomitant histological subtypes present in our case, hobnail PTC is a particularly rare variant (approximately 1% of PTC) [ 19 ], with frequent BRAF, p53, and hTERT mutations [ 127 ], usually adopting an aggressive clinical course with distant metastases, RAI refractoriness, and mortality in a significant subset of patients has been reviewed elsewhere [ 34 ]. The identification of malignancy patterns of growth (solid, trabecular, or insular) is usually the first hint of the diagnosis of PDTC.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent WHO guidelines, the tumor must contain at least 30% of cells with hobnailmicropapillary characteristics in order to be classified as an HVPTC [4,5]. Although, if the hobnail component is less than the cutoff, this is 5-30%, it is still essential to identify and mention it in the final report of the patient as it is associated with adverse prognostic significance [5][6][7]. Several studies show that tumors with ≥30% hobnail morphology had more chances for developing lymph node metastases compared to those with <30% hobnail morphology [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that HVPTC is most commonly associated with BRAF V600E mutations followed by TP53 mutations in a lesser fraction of these tumors [5][6][7]. Studies showed there are an increased risk of local recurrences and a 5.3-fold higher rate of recurrence in the tumors which have 30% or more BRAF V600E allele [5,6]. The risk of distant spread is also increased with the lung and bone being the most frequent sites of metastases [7].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis conducted in 2022 by Spyroglou et al [55 ▪ ] highlighted hobnail variant was associated with larger tumours, frequent ETE, LNM, distant metastases and increased mortality. Interestingly, the percentage of hobnail cells did not appear to have an additional effect on mortality, suggesting that the presence or absence of the hobnail component itself might be crucial for survival.…”
Section: Hobnail Variantmentioning
confidence: 99%